2010
DOI: 10.1101/gad.1984210
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of the PR-Set7 histone methyltransferase is required for normal cell cycle progression

Abstract: Although the PR-Set7/Set8/KMT5a histone H4 Lys 20 monomethyltransferase (H4K20me1) plays an essential role in mammalian cell cycle progression, especially during G2/M, it remained unknown how PR-Set7 itself was regulated. In this study, we discovered the mechanisms that govern the dynamic regulation of PR-Set7 during mitosis, and that perturbation of these pathways results in defective mitotic progression. First, we found that PR-Set7 is phosphorylated at Ser 29 (S29) specifically by the cyclin-dependent kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 37 publications
6
118
0
5
Order By: Relevance
“…This was confirmed by an independent study [52]. These results are consistent with the findings that H4K20me2-3, established by the Suv4-20 enzymes, requires H4K20me1 [53], which is catalyzed by PR-Set7, whose expression is cell cycle-regulated and present from G2 to early G1 [54][55][56][57][58].…”
Section: Replication-independent Modification "Maturation" On Newly Dsupporting
confidence: 80%
“…This was confirmed by an independent study [52]. These results are consistent with the findings that H4K20me2-3, established by the Suv4-20 enzymes, requires H4K20me1 [53], which is catalyzed by PR-Set7, whose expression is cell cycle-regulated and present from G2 to early G1 [54][55][56][57][58].…”
Section: Replication-independent Modification "Maturation" On Newly Dsupporting
confidence: 80%
“…At least three substrates (CDT1, p21, and SET8) have known roles in mitosis (21)(22)(23)64), and it is possible that other CRL4 CDT2 substrates also have mitotic roles, making general substrate stabilization important for mitosis. Independent of these mitotic roles, the known substrates of replication-cou-FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…Depleting SET8 from asynchronous cells leads to multiple defects, including not only inefficient origin licensing in G 1 but also impaired chromatin condensation in mitosis. Thus far, these phenotypes have all been attributed to the loss of SET8-deposited histone H4K20me1 (3,23,62). However, it is not yet known whether the mitotic defects from SET8 depletion are due to the absence of SET8 specifically during G 2 and mitosis or if they arise secondarily from the absence of SET8 in a prior cell cycle phase, such as G 1 .…”
Section: De Novo Set8 Reaccumulation Is Essential For Normal Mitotic mentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggested that the changes in H4K20me1 are due to parallel cell cycle changes in SETD8 protein levels. In this regard, SETD8 was found to be degraded in late G 1 -phase by the proteasome through CRL4 Cdt2 ubiquitin-mediated destruction (45)(46)(47)(48)(49)(50). Like several other cell cycle-regulated proteins, SETD8 carries two PCNA-interacting protein domains (51).…”
Section: H4k20me3mentioning
confidence: 99%